STUDI BENTUK PUSAT EDUKASI DAN PENGOLAHAN SAMPAH PLASTIK DI KAWASAN MUARA ANGKE - Vanessa, Vanessa; Hadiwono, Alvin (Jurusan Arsitektur dan Perencanaan, 2025)
Muara Angke, a central port and fisheries area on the northern coast of Jakarta, holds significant economic and social value. However, this area faces the problem of plastic waste pollution originating from ship activities, port operations, drainage systems, and community practices of indiscriminately disposing of waste. The plastic waste ultimately contaminates the waters, disrupting marine ecosystem balance, threatening public health, and jeopardizing the livelihoods that depend on marine resources. To address these issues, solutions are needed through the integration of technology and architectural design. This study responds to these problems by developing a design for a center dedicated to plastic waste education and processing, applying a regenerative architectural approach that not only focuses on environmental restoration but also strengthens the relationship between the community and its environment. The form-generation method used integrates the results of experiments on the characteristics of plastic waste types such as HDPE, PS, and PET, based on their processing methods. Plastic materials are not only processed functionally but also explored for their potential to shape architectural mass. The outcomes of these experiments will then be translated into the form and spatial composition of the building, illustrating the transition from waste to a new resource. This approach aims to create spaces that are educational and participatory, supporting comprehensive regeneration of the area. Thus, the building will demonstrate that plastic waste management is not only about solving pollution problems but can also shape the identity of the education and processing center itself. Keywords: education; plastic; processing; regenerative; waste Abstrak Muara Angke, kawasan pusat pelabuhan dan perikanan di pesisir Jakarta Utara memiliki nilai ekonomi dan sosial yang penting. Namun, di kawasan ini terdapat permasalahan pencemaran sampah plastik berasal dari aktivitas kapal, pelabuhan, drainase, dan aktivitas masyarakat yang membuang sampah secara sembarangan. Sampah plastik akhirnya mencemari perairan yang dapat mengganggu keseimbangan ekosistem laut, kesehatan masyarakat dan mata pencaharian yang bergantung pada hasil laut. Untuk mengatasi permasalahan tersebut, diperlukan solusi melalui pendekatan teknologi dan desain arsitektur. Studi ini merespons permasalahan tersebut melalui pembentukan bentuk untuk pusat edukasi dan pengolahan sampah plastik dengan pendekatan arsitektur regeneratif yang tidak hanya berorientasi pada perbaikan lingkungan tetapi juga pada hubungan antara masyarakat dan lingkungan. Metode pembentukan bentuk yang digunakan adalah intergrasi dari hasil eksperimen terhadap karakteristik sampah plastik seperti tipe HDPE, PS, dan PET yang berdasar dari proses pengolahan sampah plastik. Material plastik tidak hanya diolah secara fungsional, tetapi juga dieksplorasi potensi dalam membentuk massa secara arsitektural. Hasil eksperimen tersebut kemudian akan diterjemahkan ke dalam pengolahan bentuk dan susunan massa bangunan yang menunjukan proses transisi dari limbah menjadi sumber daya baru dan menjadikannya massa yang memiliki fungsi edukatif dan partisipatif, yang mendorong regenerasi kawasan secara menyeluruh. Dengan demikian, bangunan nantinya akan menunjukkan bahwa pengolahan plastik tidak hanya menyelesaikan persoalan limbah, tetapi juga dapat membentuk identitasi dari pusat edukasi dan pengolahan sampah plastik itu sendiri.